Boll distribution in the cotton canopy is affected by nitrogen management and cover crops in a sandy soil under water scarcity - Cordeiro, Carlos Felipe dos Santos [UNESP]; Raphael, Juan Piero Antonio [UNESP]; Echer, Fábio Rafael (Elsevier, 2024)
Context or problem: A favorable cotton boll distribution within the plant canopy can promote early fruit retention and increase crop yield and fiber quality, particularly in rainfed crops in sandy soils that are subject to periodic water deficits. However, the effects of different cover crop rotation systems combined with different nitrogen (N) rates and sources on boll distribution and cotton earliness are unknown. Objective or research question: The objective of this study was to evaluate the boll distribution and earliness of cotton as a function of the cover crop rotation system and N sources and rates, in a sandy soil of a tropical region of Brazil prone to drought. Methods: A field study was carried out for two growing seasons (2018–2020) in southeastern Brazil in an area with sandy soil. The treatments consisted of the following crop rotation systems, which were implemented in 2016: Fallow; single grass; grass + grass; grass + legume; and MIX (grass+legume+grass). In addition, N rates of 70, 100, and 130 kg ha−1 (applied as topdressing) and two N sources (urea; and controlled-release urea, CRU) were evaluated. Results: Low water availability in the 2018/2019 crop season resulted in early plants that reached 95% boll yield below fruiting node 12 when 70 kg ha−1 N (urea) was applied. Satisfactory rainfall in the 2019/2020 crop season resulted in 95% boll yield below fruiting node 14 when 130 kg ha−1 N was applied for all N sources and rotation systems. Applying CRU increased the boll distribution in the top third of the plant. Applying 130 kg ha−1 N increased the boll distribution in the middle and top thirds of the plant, particularly in the treatments with legume cover crops and CRU. In the crop season with higher rainfall and yield potential, the rotation systems without legumes that received 70 kg ha−1 N (urea) had a lower boll distribution in the top third of the plant. Conclusions: Cotton boll distribution is affected by cover crop rotation systems, N rates and sources and water availabity throughout the season. The best strategy for improving early boll setting is to apply lower rates of N as CRU in a rotation system with a mixture of grasses and legumes as cover crops. Additionally, there is still a challenge to increase the cotton earliness in years with high water availability. Implications or significance: Cover crops and increased efficiency fertilizers are important to improve boll setting throughout the entire cotton canopy. Because these technologies improve the availability of nitrogen and water in the soil, especially in dry years. Improving cotton earliness is still a challenge in low-altitude regions, since plant cycle is naturally short in these environments, due to the greater accumulation of degrees days. Even so, the use of lower N rates associated with cover crops and controlled-release urea may have a small increase in cotton earliness, but mainly help in early fruit retention.
Keywords: Controlled-release urea; Nitrogen; Plant mapping; Production systems